Towards the detection of dietary cereal processing through absorbed lipid biomarkers in archaeological pottery. (May 2018) - Hammann, Simon; Cramp, Lucy J.E.
Abstract: The uptake of cereal agriculture in the Neolithic is one of the most important processes in later human prehistory. However, in many parts of Europe, early evidence from pollen or macrofossils is scarce or inconclusive, and there are considerable ambiguities about timing, intensity and the mode of transition to agriculture in these regions. An alternative approach is organic residue analysis, a technique that targets lipids preserved in the walls of unglazed ceramic pots used for storage and processing of foodstuffs. By analysing the molecular and isotopic composition of absorbed lipid residues, many different food items and processing techniques can be detected and distinguished. However, this approach is by-and-large limited to animal-based food sources, and despite their importance, many plant-based food items including cereals are currently not accessible with this approach. For a better understanding of the behaviour of cereal lipids, cooking experiments were conducted and the uptake of cereal-specific compounds such as alkylresorcinols and plant sterols into the ceramic matrix was investigated using a new sensitive method based on GC-Q-ToF-MS. Furthermore, changes in the lipid composition through post-burial degradation was assessed by incubation of potsherds dosed with cereal lipids at 35 °C in compost. The cooking experiments showed that only small quantities of cereal lipids are liberated, but additional lipid sources (meat) can increase the transfer of cereal biomarkers into the ceramic matrix. Anoxic degradation conditions allowed for twentyfold higher levels of alkylresorcinols and twofold higher levels of plant sterols after 20 weeks compared to oxic conditions. Therefore, samples from anoxic burial environments should be targeted and high sensitivity methods are a necessity to detect the trace amounts of cereal-specific biomarkers. To test the applicability of these biomarkers for archaeological pottery, organic residues from ten coarse ware vessels from an anoxic burial context at Vindolanda were analysed. Plant sterols and stanols were detected in three sherds, and two of the sherds also contained traces of alkylresorcinols. Highlights: Cereals were cooked in ceramic pots in water, milk and together with pork meat. Alkylresorcinol uptake into the pots was between 0.2 μg/g (water) and 1 μg/g (pork). Microbial degradation was simulated through incubation of potsherds in compost. Anoxic conditions allowed the preservation of plant sterols and alkylresorcinols. Cereal biomarkers could be detected in Roman potsherds from Vindolanda.